Dampak Pengekangan Orang Tua terhadap Pembentukan Karakter Anak - Iqbal Al-Fathoni, Moh; Ashfiya Farhanah, Nurul; Shoffah Shofiyatus Salamah, Nyimas (Integritas Terbuka: Peace and Interfaith Studies, 2023)
This research focuses on the causes and effects of parents' restraint on the formation of children's character through the perspective of Johan Galtung's theory and also hadith. The purpose of this research is to find out more about the triggers of parents to restrain their children, to find out the impact on children, and to find out how this incident happened. The method used in this research is to use qualitative methods by collecting data using interview techniques and literature research. The results of this study indicate that children who receive restraint from their parents tend to feel very limited by all the rules and limited communication with others. the impact of restraint by parents can be seen from the behavior and communication style of a child.